Presentation and outcome of Gastric Cancer at a Tertiary Care Center - Sushil Bahadur Rawal; Shreesuna Katila; Samyog Adhikari; Uttam Laudari; Shrekshya Khadka; Jyoti Rayamajhi; Srijan Malla (Journal of Society of Surgeons of Nepal, 2024)
Introduction: Gastric cancer is the fifth most common cancer globally and the fourth leading cause of cancer-related deaths. Early-stage disease can be managed with endoscopic therapy or surgery, while advanced gastric cancer requires a multimodal treatment approach, including extensive lymphadenectomy. This study aims to evaluate the clinicodemographic profile and treatment outcomes of gastric cancer patients and to establish an effective therapeutic strategy.